Stereotipi di genere nelle aule di giustizia e vittimizzazione secondaria: analisi del Caso J.L.C. Italia - Valeria Tevere; Anna Iermano (Culture e Studi del Sociale)
The use of gender stereotypes is an obstacle to a full equality and causes forms of gender-based violence. In the courtrooms, although gender sensitive judicial interpretations are now spreading, there are decisions in which the asymmetrical cultural models of male domination are strongly rooted. Recently a ruling by the Court of Appeal of Florence for the acquittal of the defendants of the crime of sexual violence has caused discussion. The victim turned to the Court of Strasbourg (case of J.L. c. Italy) which condemned the Italian State, for violation of article 8 of the ECHR, for failing to protect the private life of the applicant, subjected to secondary victimization. For the Strasbourg judges, who also refer to the Grevio report on Italy, judicial actions and criminal sanctions play a crucial role in the institutional response to gender-based violence and in the fight against gender inequality. Therefore, it is essential that they avoid reproducing sexist stereotypes in judicial decisions, downplaying gender-based violence and exposing women to secondary victimization by using blaming and moralizing statements to discourage victims' confidence in justice.